Formation of gradient porous composites from preceramic papers with Ti3SiC2powder filler - Mingazova, Y. R.; Kashkarov, E. B.; Syrtanov, M. S.; Sedanova, E. P.; Krotkevich, D. G.; Travitzky, N. (Journal of Physics: Conference Series, 2021)
This article is devoted to fabrication of gradient Ti3SiC2-based composites using preceramic papers as a feedstock. The initial raw material is a stack of preceramic paper with a Ti3SiC2 powder filler, the content of which varies from 60 to 90% every three layers. The composites were obtained by spark plasma sintering (SPS) method at 10 MPa pressure for 10 min holding time. The sintering temperature was 1250 C. The microstructure and phase composition of the obtained gradient composites were analyzed.
CRIS-Team Scopus Importer:2021-08-27